Sex differences in pre-hospital analgesia and outcomes in patients presenting with acute coronary syndromes. (14th October 2021) - Nan Tie, E; Fernando, H; Nehme, Z; Dinh, D; Andrew, E; Brennan, A; Zaman, S; Liew, D; Stephenson, M; Lefkovits, J; Peter, K; Duffy, S J; et al.
Abstract: Background: Opioid analgesia remains the mainstay of pain management in acute coronary syndromes (ACS). Significant sex differences persist in ACS presentation, management and outcomes, but the impact of sex-differences on pre-hospital pain management of ACS with opioids is unknown. There is increasing awareness of the importance of pre-hospital factors in ACS, as well as emerging concerns with opioid use impairing the gastrointestinal absorption of oral P2Y12 inhibitors. Purpose: This study examined if sex-differences in pre-hospital pain scores, opioid administration and clinical outcomes exist in ACS patients. Methods: Patients presenting with ACS via ambulance (2014–2018) that underwent percutaneous coronary intervention (PCI) were prospectively collected via the Victorian Cardiac Outcomes Registry (VCOR), the Melbourne Interventional Group (MIG), and linked to the Ambulance Victoria database. The primary outcome was 30-day major adverse cardiac events (MACE). Secondary outcomes were descriptive analyses of pre-hospital pain score, intravenous morphine equivalent analgesic dosing, plus predictors of MACE and Thrombolysis In Myocardial Infarction (TIMI) 0–1 flow pre-PCI using logistic regression. Results: 10, 547 patients were included (female: 2, 775 [26.3%]). Opioids were administered to 1, 585 (57%) females and 5, 068 (65%) males (p<0.001). Adjusted 30-day MACE was similar between opioid groups in both sexes (female: OR 1.21, CI 0.82–1.79, p=0.34; male: OR 0.89, 0.68–1.16, p=0.40). Median pain score at presentation was 6 (IQR 4, 8) for both sexes. Median opioid dose was 2.5 mg (IQR 0, 10) in females and 5 mg (IQR 0, 10) in males (p<0.001), with similar pain relief achieved. Adjusted rates of TIMI 0–1 pre-PCI were higher in patients administered opioids (female: OR 2.83, CI 2.14–3.56, p<0.001; male: OR 2.95, CI 2.49–3.49, p<0.001). Conclusions: Female patients undergoing PCI received less opioid analgesia, but no sex-differences in pre-hospital pain scores were seen. Opioid administration was associated with impaired antegrade flow in the culprit artery in both sexes, but not short-term MACE. Randomised trials evaluating the clinical implications of opioid administration in ACS with sex subgroup analyses are needed to guide clinical practice. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Melbourne Interventional GroupVictorian Cardiac Outcomes Registry